PPARγ and Proline Oxidase in Cancer - Phang, James M. (Hindawi Publishing Corporation, 2008)
Proline is metabolized by its own specialized enzymes with their own tissue and subcellular localizations and mechanisms of regulation. The central enzyme in this metabolic system is proline oxidase, a flavin adenine dinucleotide-containing enzyme which is tightly bound to mitochondrial inner membranes. The electrons from proline can be used to generate ATP or can directly reduce oxygen to form superoxide. Although proline may be derived from the diet and biosynthesized endogenously, an important source in the microenvironment is from degradation of extracellular matrix by matrix metalloproteinases. Previous studies showed that proline oxidase is a p53-induced gene and its overexpression can initiate proline-dependent apoptosis by both intrinsic and extrinsic pathways. Another important factor regulating proline oxidase is peroxisome proliferator activated receptor gamma (PPARγ). Importantly, in several cancer cells, proline oxidase may be an important mediator of the PPARγ-stimulated generation of ROS and induction of apoptosis. Knockdown of proline oxidase expression by antisense RNA markedly decreased these PPARγ-stimulated effects. These findings suggest an important role in the proposed antitumor effects of PPARγ. Moreover, it is possible that proline oxidase may contribute to the other metabolic effects of PPARγ.